IL-17 Inversely Correlated with IL-10 via the STAT3 Gene in Pneumocystis-Infected Mice - Rong, Heng-Mo; Qian, Xiao-Jun; Zhang, Chao; Li, Ting; Tong, Zhao-Hui (Mediators of Inflammation, 2019)
Background. Pneumocystis pneumonia (PCP) remains a common opportunistic infection in immunosuppressed individuals. Current studies showed that multiple immune cells and cytokines took part in the host defense against Pneumocystis (PC). However, the roles of IL-17 and IL-10 in the development of PCP have not been elucidated. Methods. IL-10 and IL-17 levels in serum from PCP mice were detected via ELISA. The percentages of B10 cells, IL-10+ macrophages, and IL-10+ T cells in the lung from IL-17–/– PCP mice and Th17 cells and IL-17+ γδT cells in IL-10–/– PCP mice were examined via flow cytometry. Also, antibody neutralization examination was also performed to elucidate the relationship of IL-17 and IL-10 in the PCP model. Results. We noted the increase of IL-17 and IL-10 levels in serum from mice infected with Pneumocystis. Furthermore, deficiency of IL-17 or IL-10 could lead to the delayed clearance of Pneumocystis and more severed lung damage. Our data also demonstrated that IL-17 deficiency enhanced the serum IL-10 level and the percentages of B10 cells, IL-10+ macrophages, and IL-10+ T cells in the lung from PCP mice. Interestingly, we also noted an increase of the IL-17 level in serum and Th17 cell and IL-17+ γδT cell percentages in the lung from IL-10–/– PCP mice. Using antibody neutralization experiments, we found that the STAT3 gene might play a critical role in the interplay of IL-17 and IL-10 in PCP. Conclusion. Taken together, our results demonstrated that IL-17 and IL-10 could play the protective roles in the progression of PCP and the inverse correlation of them might be mediated by STAT3.